Implementasi Sistem Informasi Perekrutan Karyawan Berbasis Web pada PT Citra Wahana Nusantara Unit Dua Kelinci - Regizka Ayu Mega Saputri; Eko Darmanto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
PT Citra Wahana Nusantara Unit Dua Kelinci is a labor outsourcing company recruits an average of 40 employees per day. The recruitment process is still conducted using conventional methods, including manual registration, the management of applicant data that is not yet integrated, and the delivery of information via messaging applications such as WhatsApp. This makes the selection process less efficient, prone to registration errors, and difficult to monitor the status of applications in real time. This study aims to design and build a web-based Employee Recruitment Information System, equipped with online registration, test scheduling, application tracking, and Fixed-Term Employment Contract (FTE) management, to improve the efficiency of human resource management. This study employs an applied research approach using the waterfall (a sequential software development lifecycle model) system development method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. Data collection was carried out through direct observation, interviews with the Human Resources Department, and literature reviews. The system was developed using the PHP programming language with a MySQL database. The study results demonstrate that the developed system integrates the entire recruitment process onto a single digital platform, from online registration, document verification, and test scheduling, to real-time tracking of application status and the management of employment contracts. This study recommends implementing an integrated information system as a solution for digitizing human resource management, especially in outsourcing companies with high recruitment volumes.